Effects of a Low-Dose Cardiac Rehabilitation Program on Cardiovascular Conditioning Parameters in Patients with Heart Disease - Reyes, Pablo; Mejía Melara, Quirino; Saldívar Ramírez, José Onan; Solís, José; Tienda López, Fernando; Flores Ramírez, Ramiro (International Journal of Medical Students, 2025)
BACKGROUND: Cardiac rehabilitation is a high-evidence ischemic heart disease. The optimal dose of rehabilitation is not well defined due to the heterogeneity of studies. AIM: To evaluate the effects of low-dose cardiac rehabilitation on cardiovascular performance parameters in patients with heart disease. METHODS: A longitudinal, retrospective, observational, and analytical study was conducted. Adult patients who enrolled in the cardiac rehabilitation program were included, excluding or removing those without a history of cardiovascular disease, those who did not complete at least 5 rehabilitation sessions, and those with less than 80% attendance at rehabilitation sessions. Results from the initial and final (comparative) conventional and/or cardiopulmonary exercise tests were obtained, which included functional capacity in METs, chronotropic response, pressor response, heart rate and blood pressure recovery, double product, presence or absence of ischemia, arrhythmias, determination of ischemic threshold, and ergospirometry parameters such as peak VO2, VE/VCO2, O2 pulse, and aerobic and anaerobic thresholds. RESULTS: A total of 32 patients were included, of whom 65.6% were male. A significant increase was observed in peak VO2 achieved (20.7 vs. 24.2 ml/kg/min, p=<0.001) and the percentage of predicted VO2 achieved (76.3% vs. 94.5%, p=<0.001) when comparing initial and final maximal exercise tests. Improvement was found in ergometric performance indices, FC/W index (1.18 vs. 1.02, p=0.043) and DP/W index (1.78 vs. 1.39, p=0.041). No significant difference was found regarding pressor or chronotropic response parameters, heart rate and blood pressure recovery, or double product. CONCLUSION: It was concluded that in patients with heart disease, a low-dose cardiac rehabilitation program is effective in improving cardiovascular conditioning parameters such as peak VO2 and reducing the ischemic threshold